Timed soft concurrent constraint programs: An interleaved and a parallel approach. Issue 6 (November 2015) - BISTARELLI, STEFANO; GABBRIELLI, MAURIZIO; MEO, MARIA CHIARA; SANTINI, FRANCESCO
Abstract We propose a timed and soft extension of Concurrent Constraint Programming. The time extension is based on the hypothesis of bounded asynchrony: The computation takes a bounded period of time and is measured by a discrete global clock. Action prefixing is then considered as the syntactic marker that distinguishes a time instant from the next one. Supported by soft constraints instead of crisp ones, tell and ask agents are now equipped with a preference (or consistency) threshold, which is used to determine their success or suspension. In this paper, we provide a language to describe the agents' behavior, together with its operational and denotational semantics, for which we also prove the compositionality and correctness properties. After presenting a semantics using maximal parallelism of actions, we also describe a version for their interleaving on a single processor (with maximal parallelism for time elapsing). Coordinating agents that need to take decisions on both preference values and time events may benefit from this language.